2018
DOI: 10.1002/chem.201800730
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Dehydrogenative Phenothiazination of Phenols

Abstract: The straightforward capture of oxidized phenothiazines with phenols under aerobic conditions represents a unique cross‐dehydrogenative C−N bond‐forming reaction in terms of operational simplicity. The mechanism of this cross‐dehydrogenative N‐arylation of phenothiazines with phenols has been the object of debate, particularly regarding the order in which the substrates are oxidized and their potentially radical or cationic nature. Understanding the selective reactivity of phenols for oxidized phenothiazines is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 67 publications
1
26
0
3
Order By: Relevance
“…Die jeweiligen ESR-Spektren sind in Abbildung 2 dargestellt. Aufgrund von früheren Studien haben wir vergleichbare N-zentrierte neutrale Radikale für alle vier Kongenere erwartet, [17] jedoch weisen nur die ersten drei (X = O, S, Se) ESR-Signale auf eine Spezies mit Nzentriertem Radikal PXZC hin (Abbildung 2). Hingegen zeigt Phenotellurazin ein komplett anderes ESR-Signal.…”
unclassified
See 1 more Smart Citation
“…Die jeweiligen ESR-Spektren sind in Abbildung 2 dargestellt. Aufgrund von früheren Studien haben wir vergleichbare N-zentrierte neutrale Radikale für alle vier Kongenere erwartet, [17] jedoch weisen nur die ersten drei (X = O, S, Se) ESR-Signale auf eine Spezies mit Nzentriertem Radikal PXZC hin (Abbildung 2). Hingegen zeigt Phenotellurazin ein komplett anderes ESR-Signal.…”
unclassified
“…Dieser Prozess wird durch die basischen Bedingungen und/oder das Peroxidanion, das sich aus der Reduktion von O 2 bildet, begünstigt (Schema 5, siehe auch SI). Durch den HAT werden sowohl die Bildungsgeschwindigkeit als auch die Konzentration des neutralen Radikals PSZC erhçht, welches ein bekanntes Intermediat der dehydrierenden Phenothiazierungsreaktion ist, [17] wodurch die die…”
unclassified
“…However, the radicalradical recombination and regeneration of nitrosonium species would occur in the same manner. [85] Scheme 34 Sustainable C-H/N-H cross-coupling for the C-H bond amination of phenols.…”
Section: Scheme 33 Nitronium Salts As Efficient Catalysts For C-h/s-hmentioning
confidence: 99%
“…The methylene blue radical was postulated in 1939 and later supported by evidence from combined electrochemical and EPR studies, which revealed a high tendency toward disproportionation . Although some persistent N‐unsubstituted phenothiazinyl radicals permitted spectroscopic characterization, the isolation of a crystalline and air‐stable derivative has, to the best of our knowledge, never been accomplished …”
Section: Introductionmentioning
confidence: 99%